Gardnerella vaginalis as a Cause of Bacterial Vaginosis: Appraisal of the Evidence From in vivo Models - Morrill, Sydney; Gilbert, Nicole M.; Lewis, Amanda L. (Frontiers in Cellular and Infection Microbiology, 2020)
Koch's postulates dictate the use of experimental models to illustrate features of human disease and provide evidence for a singular organism as the cause. The underlying cause(s) of bacterial vaginosis (BV) has been debated in the literature for over half a century. In 1955, it was first reported that a bacterium now known as Gardnerella vaginalis may be the cause of a condition (BV) resulting in higher vaginal pH, thin discharge, a fishy odor, and the presence of epithelial cells covered in bacteria. Here we review contemporary and historical studies on BV with a focus on reports of experimental infections in human or animal models using Gardnerella vaginalis. We evaluate experimental evidence for the hypothesis that G. vaginalis is sufficient to trigger clinical features of BV or relevant health complications associated with the condition. Additionally, we evaluate in vivo models of co-infection employing G. vaginalis together with other bacterial species to investigate evidence for the hypothesis that G. vaginalis may encourage colonization or virulence of other potential pathogens. Together, these studies paint a complex picture in which G. vaginalis has both direct and indirect roles in the features, health complications, and co-infections associated with BV. We briefly review the current taxonomic landscape and genetic diversity pertinent to Gardnerella and note the limitations of sequence-based studies using different marker genes and priming sites. Although much more study is needed to refine our understanding of how BV develops and persists within the human host, applications of the experimental aspects of Koch's postulates have provided an important glimpse into some of the causal relationships that may govern this condition in vivo.